MOTIVASI EKSTRINSIK MAHASISWA DALAM MEMILIH PROGRAM STUDI PENDIDIKAN AGAMA ISLAM UNIVERSITAS ISLAM NEGERI AR-RANIRY BANDA ACEH DAN IMPLIKASINYA TERHADAP HASIL BELAJAR - Ariska Ariska; Mashuri Mashuri (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
Extrinsic motivation is one of the important factors that can influence students in continuing their studies, especially in choosing a study program, including the Islamic Education (PAI) Program. External factors such as parental encouragement, job opportunities, or not being accepted into another program not only play a role in determining the choice of study program, but also have an impact on students’ learning outcomes. This study aims to identify the extrinsic motivations of the 2021 cohort students in choosing the Islamic Education Study Program and to examine the implications of these motivations for their learning outcomes. The study employed a mixed-methods approach, with quantitative data collected through questionnaires distributed to 30 students and qualitative data obtained through in-depth interviews with 3 students who had different GPA achievements. The results showed that the extrinsic motivations of the 2021 cohort students in choosing the Islamic Education Study Program were influenced by several factors, namely parental encouragement, job opportunities, environmental influences, and the reason of not being accepted into another program. The Pearson correlation test indicated a positive and significant relationship between extrinsic motivation and learning outcomes, with a correlation coefficient of r = 0.584 and p = 0.007. The qualitative findings from the interviews supported this result, showing that students with consistent parental support tended to achieve higher GPAs, while those whose extrinsic motivation decreased showed lower academic performance. Thus, extrinsic motivation is proven to make an important contribution to students’ learning outcomes.